ANALISIS PENERAPAN MEDIA PEMBELAJARAN BERBASIS E-LEARNING PADA PEMANFAATAN SMARTPHONE MATA PELAJARAN MATEMATIKA DI SMP NEGERI 1 PADANGSIDIMPUAN - NAJMI ZAHRAINI (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
This study aims to analyze the planning, process and evaluation of learning using e-learning based learning media on the use of smartphones in mathematics at SMP Negeri 1 Padangsidimpuan. This type of research is descriptive qualitative research with research subjects consisting of class VII mathematics teachers, amounting to 2 teachers and class VII students totaling 24 people with the researcher as the key instrument. The data collection procedures for this research are observation techniques, interviews, and documentation using smartphone media.The results show that, firstly in terms of planning, teachers have prepared themselves to face students properly using technology on smartphones. This can be seen from the readiness of planning archives and their compatibility with PermenDikbud No. 22 of 2019. Second, the teaching and learning process that is carried out encourages students think more critically, actively and independently in accepting the material presented. Third, the evaluation which is held every two to three times a week is going well.